1924
DOI: 10.1037/h0073265
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Reliability of the Maze with Rats and Humans.

Abstract: Maze-running experiments on both humans and rats furnish data which prove that no maze is satisfactorily analyzed with respect to all of its parts and the conditions they present to learning to allow unequivocal conclusions on individual or group differences. But after automatization in maze-running has been effected, then extraneous factors can be introduced into the maze-situation to demonstrate the presence or absence of automatism; this latter procedure is scientific. From Psych Bulletin 23:04:00281.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1924
1924
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…In working up our data, we have considered our original 82 rats as an unselected group which could be used as a standard in determining the best statistical treatment for the remaining data. As Hunter and his students (4,8,9,12) have shown, there is considerable question as to the possibility of measuring reliable individual differences in rats at all. And for that reason a discovery of the best statistical method of treating results was important.…”
Section: Statistical Tbeatment Op Results Prom Original Groupmentioning
confidence: 99%
“…In working up our data, we have considered our original 82 rats as an unselected group which could be used as a standard in determining the best statistical treatment for the remaining data. As Hunter and his students (4,8,9,12) have shown, there is considerable question as to the possibility of measuring reliable individual differences in rats at all. And for that reason a discovery of the best statistical method of treating results was important.…”
Section: Statistical Tbeatment Op Results Prom Original Groupmentioning
confidence: 99%
“…We conclude that even though the empirical evidence now at hand indicates that maze running gives low reliabilities for placing individual rats per se, this does not mean (as Hunter (7,8) suggests) that all the work that has been done in the past, using such mazes to compare mean scores of large groups of rats, or groups of rats whose performances are really far apart, should therefore also be discarded. Instead, it would appear (See also Carr (2) for a substantiation of the present point of view) that all that is necessary is: first, that the obtained differences between the means of the contrasted groups shall satisfy the statistician's criterion of being, say, three times their own sigmas* (i.e., that differences of the given size shall be liable to occur by mere chance only some 27 times out of 10,000); and, second, that the numbers in the groups shall have been large enough to allow the application of statistical criteria.…”
Section: The Significance Of Reliability Coefficientsmentioning
confidence: 95%
“…Curve B, on the other hand, is to represent an average rat, and curve C a bright one. 8 But it may perhaps be contended that such an assumption is fundamentally wrong. 9 Thus, it may be pointed out that actually we often tend to obtain not parallel individual curves, but ones which might more nearly be represented by figure 2.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…In 1924, Hunter and Randolph concluded that a simple T-maze greatly reflects the individual differences in the learning ability. By that time, the simple T-maze was the most reliable maze for the study of the habit formation in white rats ( Hunter & Randolph, 1924 ).…”
Section: Different Types Of Mazesmentioning
confidence: 99%
“…In most maze experiments, four common measures have been used to quantify the maze learning skill, including errors, time, distance, and the number of required trials to complete the maze learning process. Each of these measures has its advantages and disadvantages ( Hunter & Randolph, 1924 ). However, along with the development of various mazes, new measures have been used ( Paul, Magda, & Abel, 2009 ).…”
Section: Introductionmentioning
confidence: 99%